EXPRESSION OF LYRICAL EXPERIENCE IN THE POETRY OF GAFUR GULAM (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2024)
This article examines the expression in the poems of the academic poet Ghafur Ghulam as a child-father, a humane poet. He follows the art of the poet's poems dedicated to his children and explores the artist's ability to "infect" the reader with special experiences. The article makes some generalizations that the poet was able to turn personal family information into a subtle expression of art.